Restoration of surface waters contaminated with cyanobacterial harmful blooms (CYANO-HABs) through novel chemical oxidation processes - Keliri, Eleni (My University, 2022)
Cyanobacteria (blue-green algae) are phototrophic microorganism that represent an essential component of the food web in all aquatic ecosystems. However, the effects of climate change and anthropogenic activities have intensely increased the load of nutrients in surface waters around the globe, making cyanobacterial harmful blooming (cyano HABs) more persistent and prevalent, adding further pressure on the already scarce fresh water supply. Their overgrowth is causing undesirable odor, color, and taste to the water, as well as toxicity since certain strains of cyanobacteria are producing secondary metabolites, called cyanotoxins which are lethal to both humans and animals. Currently an array of methods has been applied to mitigate the negative effects of cyano-HABs, that differ in cost, efficiency, and environmental impact. Those can be categorized as physical, chemical, and biological treatment methods based on their application type. Chemical methods are the most applied ones for being efficient, cost effective, and having long-lasting treatment results. The most recently developed method is the use of liquid hydrogen peroxide (H2O2) in affected surface waterbodies which is by far the least hazardous chemical, among the treatment options, used for in-situ treatment. However, studies have shown that its efficiency varies based on the species type and density as well as on matrix composition. In cases of high contamination, the use of higher doses of H2O2 than the recommended > 5 mg L -1 dose, are required. which negatively impact zooplankton and other non-targeted species. In this doctoral thesis, peroxide releasing compounds were utilized to test their potency to mitigate cyano-HABs as novel treatment alternatives to the high doses of liquid hydrogen peroxide. More specifically, the following oxidants were utilized: magnesium peroxide (MgO2) granules, calcium peroxide (CaO2) granules and powder, CaO2 granules enclosed in fabrics (GEF), and peroxymonosulfate (PMS). Calcium peroxide granules enclosed in textile materials and single low doses of peroxymonosulfates outperformed liquid H2O2 treatment in terms of efficiency, required dose, and environmental friendliness. Treatment with liquid H2O2 in concentrations 1 to 5 mg L−1 had no effect on the phycocyanin fluorescence (Ft) and quantum yield of PSII (Fv/Fm) indicating an ineffective treatment for the dense (1 million cells mL−1 ± 20%) and naturally occurred Merismopedia sp. bloom, while 1 g L−1 CaO2 granules succeeded in treating the bloom. In another study, metallic peroxide granules tested for their H2O2 releasing capacity in filtered St. George Lake matrix, where they released significantly higher H2O2 concentration and therefore had better mitigation efficiency than MgO2 granules. CaO2 granules releasing capacity was also tested in three different matrixes: MQ-water, River Water and Dam water. Release kinetics results showed that matrix composition influences the H2O2 release by granules. In extra-pure water (milli-Q) the release of H2O2 was limited in comparison with its release in surface waters of CaO2 granules. For instance, dam water which was the least contaminated water, resulted in higher and continuous H2O2 yield of around 6 mg L-1 for 1 g L-1 CaO2 granules applied, whereas an equal CaO2 dose in river water with elevated physicochemical characteristics released around 5 mg L -1 H2O2, and in lake water was around 3 mg L-1 . Similar release experiments were performed in surface water spiked with humics, and BG-11 medium of different concetrations. Results have shown that humics can activate CaO2 granules through an interfacial mechanism causing the simultaneous generation of hydroxyl and hydroxyalkyl radicals. Additionally, application of CaO2 granules and liquid H2O2 in BG-11 matrices of different dilutions showed lower H2O2 availability than what expected, indicating that the presence of micronutrients and trace elements into the water can consume and/ or interact with the available H2O2. A toxicity study on invertebrate species of CaO2 granules revealed the undesirable effects on Echinogammarus veneris when applied in doses higher than 1 g L-1 . Treatment of cultivated cultures with CaO2 granules, showed that doses higher than 0.2 and 1.0 g L-1 CaO2 granules were efficient to treat Microcystis sp. and Aphanizomenon sp. in Kouris Dam matrix, respectively. Finally, treatment experiments of cyano-HABs contaminated water with PMS outperformed equal doses of liquid H2O2. Instant oxidant quantification during treatment also showed that PMS has a residual effect while H2O2 is rapidly being consumed or decomposed, supporting further the competence of PMS compared with H2O2 as a novel treatment method. Treatment experiments indicated that slow H2O2 releasing CaO2 granules, and PMS could be alternative solutions to liquid hydrogen peroxide, when applied in appropriate doses, but further investigation is needed before their field applications to ensure safety of the aquatic ecosystem.
Keywords: Cyanobacteria; Oxidant; Restoration; Surface water; Treatment